Artificial intelligence in higher-level education: A SWOT analysis and 20-year bibliometric analysis using VOSviewer - Wilber Sabado (Heritage and Sustainable Development)
Artificial intelligence (AI) is transforming the domain of higher education. A bibliometric study about this is important, especially in identifying trends and gaps that are crucial for policy development, higher education management, and future research initiatives. The two-decade analysis provided an overview of the increasing trajectory of research publications concerning artificial intelligence in higher education. This research analyzed the 5522 searched articles in the Scopus database using bibliographic analysis following a systematic approach to data collection called PRISMA. This research shows that China and the United States emerged as the leading countries in terms of publication count. Likewise, the United States, China, India, and the United Kingdom demonstrate higher levels of collaboration compared to other countries. The majority of research articles predominantly use the English language. These findings mean that AI is gaining significant popularity in the higher education sector. It is likely influencing the teaching and learning pedagogies. The VOSviewer software was used to visualize global collaboration of documents, the co-occurrence of keywords, and the co-authorships. Some of the most used keywords were also identified in this study, like “Artificial Intelligence,” “Higher Education,” “Students,” “High Education,” and “Education.” Moreover, this paper presented the SWOT analysis of the most cited papers.